Democracy, Citizen Sovereignty and Constitutional Economics - Viktor J. Vanberg (Albert-Ludwigs-Universität Freiburg, Institut für Allgemeine Wirtschaftsforschung, Abteilung für Wirtschaftspolitik, 2006)
This paper is an exercise in conceptual clarification. Its purpose is to explore the contribution that constitutional economics can make to the theory of democracy. Constitutional economics as the economics of rules is concerned with the study of how the choice of rules in the social, economic and political realm affects the nature of the processes of human interaction that evolve within these rules. The theory of democracy is concerned with institutionalorganizational problems of self-governing polities. The purpose of the paper is to examine some of the fundamental issues that are brought into focus by applying the perspective of constitutional economics to the rules and institutions of a democratic polity. Sections 1 and 2 discuss general characteristics of the constitutional economics paradigm that are of particular significance to the study of democratic institutions. Sections 3 and 4 explore the contribution that a constitutional economics perspective can make in diagnosing organizational problems of democratic polities.
Keywords: 330